Clinical, light, and electron microscopy findings in idiopathic haematuria. Issue 10 (October 1973) - Alexander, F.; Lannigan, R.; Bull, R.
Abstract : The electron microscopic findings are reported in detail in 20 patients submitted to renal biopsy with the major complaint or clinical finding of gross or microscopic haematuria. The lesions were classified histologically into four groups: group 1, minor glomerular alterations; group 2, focal mesangial thickening and/or cellular proliferation; group 3, diffuse mesangial proliferation; and group 4, other lesions. The major ultrastructural alterations included irregularity in thickness and density of the capillary basement membrane, with apparent discontinuity and bi- or multilaminar splitting of the lamina densa. There were varying degrees of foot process fusion, visceral epithelial polykaryocytosis, and granular deposits related to the capillary basement membrane. Densities were found in the mesangial basement membrane-like material, which was often markedly increased in quantity. A few microtubular aggregates were observed in endothelial cell cytoplasm. Changes consistent with acute diffuse proliferative and membrano-proliferative glomerulonephritis were also seen. The significant clinical findings, histological groups, and ultrastructural changes are correlated.